The new Blackwell companion to the city - Bridge, Gary.; Watson, Sophie (Malden, MA : Wiley-Blackwell, 2013)
"This book considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. The most interdisciplinary collection of its kind. Provides a contemporary update on urban thinking that builds on well established debates in the field Uses the city to explore economic, social, cultural, environmental and political issues more broadly. Includes contributions from non Western perspectives and cities."--
"Drawing together leading scholars from a variety of academic disciplines, this collection reports the leading edge of research and analysis into the contemporary urban condition. With more than half of the world's population living in urban environments, cities are places of huge complexity and diversity and the processes and structures that bind them together reach out across the globe. This volume considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. Whilst considering established themes, such as urban divisions and differences, publics and cultures, politics and planning, the New Blackwell Companion to the City also addresses new debates on subjects like materiality, mobilities, and environment. Incorporating international examples, this book explores the economic, social, cultural, environmental and political issues that flow from and within the modern city"--
Rev. ed. of: A companion to the city, 2000.
Bibliografske bilješke uz tekstove
Kazalo
Keywords: grad; grad -- međukulturno istraživanje